2012
DOI: 10.1521/jscp.2012.31.5.488
|View full text |Cite
|
Sign up to set email alerts
|

Staying Connected when Coming Apart: The Psychological Correlates of Contact and Sex with an Ex-Partner

Abstract: Although marital separation is an inherently social experience, most research on adults’ psychological adjustment following a romantic separation focuses on intrapersonal characteristics, or individual differences (e.g., attachment style, personality, longing) that condition risk for poor psychological outcomes. We know little about how these individual differences interact with interpersonal processes, such as contact between ex-partners. In the current study, we sought to understand how adults’ continued att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Psychological outcomes after ongoing contact with an ex-partner are likely moderated by a range of variables, including relationship orientations (e.g., attachment insecurity), individual psychological processes (e.g., a history of major depressive disorder and a tendency toward maladaptive repetitive thinking; Davis, Shaver, & Vernon, 2003; Lee, Sbarra, Mason, & Law, 2011; Sbarra et al, 2014), as well as ongoing attachment to a former partner (see Borelli, Sbarra, & Mehl, 2019). For example, a study investigating the effects of ongoing contact with an ex-partner after marital separation found that the association between contact and psychological adjustment was moderated by the degree to which individuals had accepted their separation; adults who remained in contact with their ex-partner and were less accepting of the separation exhibited poorer adjustment compared with adults with higher levels of separation acceptance (Mason, Sbarra, et al, 2012). The continued search for substantive moderators is a key direction for research in this area (Mason & Sbarra, 2012).…”
Section: The Person and The Context: The Moderating Role Of Individuamentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological outcomes after ongoing contact with an ex-partner are likely moderated by a range of variables, including relationship orientations (e.g., attachment insecurity), individual psychological processes (e.g., a history of major depressive disorder and a tendency toward maladaptive repetitive thinking; Davis, Shaver, & Vernon, 2003; Lee, Sbarra, Mason, & Law, 2011; Sbarra et al, 2014), as well as ongoing attachment to a former partner (see Borelli, Sbarra, & Mehl, 2019). For example, a study investigating the effects of ongoing contact with an ex-partner after marital separation found that the association between contact and psychological adjustment was moderated by the degree to which individuals had accepted their separation; adults who remained in contact with their ex-partner and were less accepting of the separation exhibited poorer adjustment compared with adults with higher levels of separation acceptance (Mason, Sbarra, et al, 2012). The continued search for substantive moderators is a key direction for research in this area (Mason & Sbarra, 2012).…”
Section: The Person and The Context: The Moderating Role Of Individuamentioning
confidence: 99%
“…A study of young adults who recently experienced a romantic breakup reported higher levels of both love and sadness on days that they were in contact with their ex-partners (Sbarra & Emery, 2005b), which makes the story more complicated. In a more recent study, nonsexual contact with an ex-partner after termination of a nonmarital romantic relationship was associated with poorer adjustment, but only in adults reporting lower levels of acceptance (Mason, Sbarra, Bryan, & Lee, 2012). Other studies have found no association between ongoing contact with an ex-partner and psychological outcomes (Masheter, 1997).…”
mentioning
confidence: 99%
“…Such contact might result in perpetuating individuals’ conflicting thoughts and feelings about ex-partners, which could hamper their daily well-being and functioning (Sbarra & Emery, 2005). Research on self-expansion theory as well as relationship contingent self-esteem also suggests that losing more of our self-concepts after relationship dissolution complicates breakup recovery (Lewandowski et al, 2006; Rodriguez et al, 2016), and this loss of self after a breakup might make individuals more susceptible to ambivalence because maintaining connection might assuage their identity loss (Mason et al, 2012). Cognitive dissonance theory (Festinger, 1957) also suggests that having inconsistent thoughts regarding an ex-partner causes an internal tension and discomfort as we prefer to have consistent beliefs and attitudes (see also Elliot & Devine, 1994; Levy et al, 2018).…”
Section: Relational Ambivalence and Post-dissolution Distressmentioning
confidence: 99%
“…But the more typical case—at least for relationships that have reached the established relationship stage—is that the decision to break up transpires over the course of days, weeks, months, or even years. In addition, following the decision to break up, the two partners sometimes stay in touch, experience deep emotional intimacy, and even have sex (Davis, Shaver, & Vernon, 2003; Mason, Sbarra, Bryan, & Lee, 2012; Spielmann, Joel, MacDonald, & Kogan, 2013).…”
Section: The Relationship Development Model Of Sexual Desirementioning
confidence: 99%